Implementation of Islamic Business Ethics in Persis Banjaran Jam'iyah Enterprises - Nurfahmiyati Nurfahmiyati; Rini Lestari; Kania Nurcholisah; Asri Suangga; Asyifa Nur Azizah; Wijaya Handoyo; Dimas Nurjaya (Universitas Islam Bandung, 2022)
This study aims to determine the application of Islamic business ethics and dimensions based on four traits of the Apostle (Shiddiq, Amanah, fathonah, and Tabligh) to Jam'iyyah Persis Banjaran business actors. The research method is a descriptive qualitative analysis method carried out on independent variables without making comparisons or connecting with other variables to obtain an overview of the research variables. The results showed that the four qualities of the Apostle had been applied very well, especially in Shiddiq and Amanah. The results of processed data showed that the highest average score in Islamic business ethics was 4.58. Judging from the four qualities of the Apostle applied by business actors in Persis Banjaran, the Shiddiq dimension value is the highest, 4.68. Meanwhile, the value of the Amanah dimension is 4.59.